Colorectal Cancer From Pathophysiology to Novel Therapeutic Approaches - Barresi, Valeria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Colorectal cancer is one of the most common malignancies worldwide, and the pathogenesis of this neoplasm is probably one of the most studied. The knowledge obtained over time has led to the development of screening and early diagnosis systems, allowing a significant reduction in the incidence of this neoplasm. However, what is currently known probably represents only the tip of the iceberg of the biology of this tumor. It was recently shown that the gut microbiota may contribute to colorectal cancerogenesis. In addition, several novel targeted therapies are now applied to patients with colorectal carcinoma. Nonetheless, several questions are still unanswered. Could the modulation of the gut microbiota modify the risk of tumor progression or the efficacy of therapies? Are there any predictive biomarkers of the risk of tumor progression or the efficacy of target therapies? Is metastatic colorectal cancer one or more diseases? This book collects a series of scientific articles reflecting part of the state of the art regarding colorectal cancer, seeking to answer these questions.